A Structured Assessment to Decrease the Amount of Inconclusive Endometrial Biopsies in Women with Postmenopausal Bleeding. (13th March 2016) - Breijer, M. C.; Visser, N. C. M.; van Hanegem, N.; van der Wurff, A. A.; Opmeer, B. C.; van Doorn, H. C.; Mol, B. W. J.; Pijnenborg, J. M. A.; Timmermans, A.
Abstract : Objective. To determine whether structured assessment of outpatient endometrial biopsies decreases the number of inconclusive samples. Design. Retrospective cohort study. Setting. Single hospital pathology laboratory. Population. Endometrial biopsy samples of 66 women with postmenopausal bleeding, collected during the usual diagnostic work-up and assessed as insufficient for a reliable histological diagnosis. Methods. Endometrial biopsy samples were requested from the pathology laboratories. The retrieved samples were systematically reassessed by a single pathologist specialized in gynecology. Main Outcome Measure. Disagreement between initial assessment and conclusion after structured reassessment. Results. We retrieved 36 of 66 endometrial biopsy samples from six different pathology laboratories. Structured reassessment of the retrieved samples by a single pathologist specialized in gynecology did not change the conclusion in 35 of the 36 samples. The remaining sample contained a large amount of endometrial tissue and the diagnosis at reassessment was endometrial hyperplasia without atypia. All other samples contained insufficient material for a reliable diagnosis. Conclusion. A structured reassessment of endometrial biopsies samples, which were classified as inconclusive due to insufficient material, did not change the conclusion. Although it might be helpful for pathologists to have diagnostic criteria for adequacy and/or inadequacy of an endometrial biopsy sample, the gain in efficiency is likely to be small.